'Because, they are from here. It is their identity, and it is important': teachers' understanding of the role of translation in vernacular language maintenance in Malekula, Vanuatu. Issue 9 (21st October 2021) - Daly, Nicola; Barbour, Julie
ABSTRACT: The idea of employing culturally and linguistically appropriate resources to address disparate literacy levels and to maintain the languages and cultures of communities in the Pacific has been presented by academics from different disciplines. In 2012, a National Language Policy was endorsed in Vanuatu, accommodating the endangered vernacular languages of Vanuatu within the formal education system for the first time in the nation's history. To implement the policy, the Ministry of Education and Training developed a plan to create vernacular resources for around half of Vanuatu's 100+ languages. On Malekula, teachers from seven local languages were involved in the implementation plan, translating a pool of regionally sourced literacy materials into their own languages. Teachers' beliefs about the place of the translated reading materials in language maintenance, and their understandings of local literacy and storytelling practices in Malekula, were sought through semi-structured interviews. The interviews reveal shared storytelling practices on Malekula, in both schools and communities. Further, the data reveal a clear awareness amongst the teachers of the important role of culturally accessible and linguistically relevant literacy materials in the maintenance of local languages and knowledge.